Spriritual Metode Spiritual Penghayat Kapribaden Dalam Menjalin Hubungan Dengan Sang Pencipta - Satria Adhitama (Kamaya: Jurnal Ilmu Agama, 2021)
There are hundreds of beliefs in Indonesia, one of which is Kapribaden. The essence of Kapribaden's teachings is a spiritual practice by starting to know yourself as a human being and after that you can only know God. Before knowing God, Kapribaden followers must understand human nature first. This study aims to dig deeper into how Kapribaden believers establish a relationship with the Creator. This study uses a constructivist paradigm with interview data collection methods and literature study. There is a method or method known as Panca Gaib or Sarana Gaib to connect Kapribaden followers with God, namely Kunci, Asmo, Mijil, Singkir, and Paweling. By understanding this, it is hoped that the public can get a clear picture of the relationship between Kapribaden followers and God, so that acts of discrimination can be minimized.